Evaluación cualitativa del crédito y su relación con el análisis económico financiero del cliente en Caja Sipán - Oficina de Huamachuco, año 2016 - Peña Segura, Pedro Orlando (2017)
The present research work has taken place in the Caja Sipán of the city of Huamachuco, Province of Sánchez Carrión, Region of La Libertad, Peru; has as main objective to determine the form of relationship between the Qualitative Evaluation of the Credit and the Financial Economic Analysis of the Client in said entity. In this respect, the research problem has been silenced: How does the Qualitative Credit Assessment and the Financial Economic Analysis of the Client relate to Caja Sipán - Oficina de Huamachuco, year 2016? In the collection of data have taken into account a population of 376 clients who maintain SME credits. The respective sample is 77 clients; of which information has been obtained through documentary analysis. According to the results obtained, and according to the scientific method, the corresponding analysis and discussion has been carried out, thus demonstrating the validity of the hypothesis that states: "The Qualitative Credit Assessment is positively and significantly related to the Economic Analysis Customer Financial in Caja Sipán - Office of Huamachuco, year 2016 ". As a final part, the conclusions and recommendations have been formulated. The main conclusion is that there has been a relationship between the variable Qualitative Evaluation of Credit and the Financial Analysis of the Client, both methods being complementary to know the capacity and disposition of the clients against their credit obligations, even more when dealing with small businesses with a certain degree of informality. Its recommendation establishes that, considering the importance of both methods (Qualitative Credit Evaluation and Financial Economic Analysis), credit analysts should be trained in the technical and ethical aspects to carry out the collection of information, to make the corresponding records, as well as Process and interpret the data obtained.